Pathways to First-Episode Care for Psychosis in African-, Caribbean-, and European-Origin Groups in Ontario. (May 2015) - Anderson, Kelly K; Flora, Nina; Ferrari, Manuela; Tuck, Andrew; Archie, Suzanne; Kidd, Sean; Tang, Taryn; Kirmayer, Laurence J; McKenzie, Kwame
Objective: To compare the pathways to care and duration of untreated psychosis (DUP) for people of Black-African, Black-Caribbean, or White-European origin with first-episode psychosis (FEP). Methods: We recruited a sample of 171 patients with FEP of Black-African, Black-Caribbean, and White-European origin from hospital- and community-based early intervention services (EIS) in the cities of Toronto and Hamilton. We compared the 3 groups on DUP and key indicators of the pathway to care. Results: We observed differences in pathways to care across the 3 groups. Black-Caribbean participants had an increased odds of referral from an inpatient unit to EIS (OR 3.33; 95% CI 1.46 to 7.60) and a decreased odds of general practitioner involvement on the pathway to care (OR 0.17; 95% CI 0.07 to 0.46), as well as fewer total contacts (exp[β] 0.77; 95% CI 0.60 to 0.99) when compared with White-European participants. Black-African participants had an increased odds of contact with the emergency department at first contact (OR 3.78; 95% CI 1.31 to 10.92). The differences in the DUP between groups were not statistically significant. Conclusions: Our findings suggest that there are significant differences in the pathways to EIS for psychosis for people of African and Caribbean origin in our Canadian context. It is essential to gain a comprehensive understanding of the pathways that different population groups take to mental health services, and the reasons behind observed differences, to inform the development of equitable services, targeting patients in the critical early stages of psychotic disorder.